Γ-Aminobutyric Acid Type A Receptor Modulation by Etomidate Analogs. (March 2016) - Pejo, Ervin; Santer, Peter; Wang, Lei; Dershwitz, Philip; Husain, S. Shaukat; Raines, Douglas E.
Abstract : Background: Etomidate is a highly potent anesthetic agent that is believed to produce hypnosis by enhancing γ-aminobutyric acid type A (GABAA ) receptor function. The authors characterized the GABAA receptor and hypnotic potencies of etomidate analogs. The authors then used computational techniques to build statistical and graphical models that relate the potencies of these etomidate analogs to their structures to identify the specific molecular determinants of potency. Methods: GABAA receptor potencies were defined with voltage clamp electrophysiology using α1 β3 γ2 receptors harboring a channel mutation (α1 [L264T]) that enhances anesthetic sensitivity (n = 36 to 60 measurements per concentration–response curve). The hypnotic potencies of etomidate analogs were defined using a loss of righting reflexes assay in Sprague Dawley rats (n = 9 to 21 measurements per dose–response curve). Three-dimensional quantitative structure–activity relationships were determined in silico using comparative molecular field analysis. Results: The GABAA receptor and hypnotic potencies of etomidate and the etomidate analogs ranged by 91- and 53-fold, respectively. These potency measurements were significantly correlated (r 2 = 0.72), but neither measurement correlated with drug hydrophobicity (r 2 = 0.019 and 0.005, respectively). Statistically significant and predictive comparative molecular field analysis models were generated, and a pharmacophore model was built that revealed both the structural elements in etomidate analogs associated with high potency and the interactions that these elements make with the etomidate-binding site. Conclusions: There are multiple specific structural elements in etomidate and etomidate analogs that mediate GABAA receptor modulation. Modifying any one element can alter receptor potency by an order of magnitude or more. Abstract : By using both in vitro and in vivo assays of etomidate action, γ-aminobutyric acid type A receptor and hypnotic potencies of etomidate and 22 etomidate analogs were significantly correlated, supporting a direct role for receptor activation in etomidate-induced hypnosis. Molecular modeling computational techniques were used to build pharmacophore models that revealed multiple structural elements associated with high-potency binding-site interactions of etomidate.